Pengembangan Algoritma Tabu Search Berbasis Bilangan Grey Untuk Optimalisasi Flexible Job Shop Dengan Ketidakpastian - R Tampubolon, Ferdinan; Siagian, Sinta; Chrisna HS, Samaria; Devita, Rischa (Jurnal Syntax Fusion, 2023)
This research aims to make a step-by-step process to determine the most optimal completion time for the Flexible Job Shop Scheduling case. Flexible Job Shop Scheduling which not only aims to sequence operations on jobs but also chooses the machine to be used in processing an operation makes this scheduling more complicated than ordinary Job Shop Scheduling. This scheduling involves interval-shaped gray numbers to accommodate uncertainty in job ordering time. This further extends the complexity of scheduling. To solve this case a metaheuristic algorithm namely Tabu Search will be used. This algorithm uses mutation on the solution a number of iterations until it produces the best solution. The use of a tabu list in the Tabu Search algorithm to ensure the search is not trapped in the local minimum.